2016
DOI: 10.13189/ujcm.2016.040101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asymptomatic Bacteriuria among the Pregnant Women Receiving Antenatal Care at Federal Medical Centre Owerri, Nigeria

Abstract: The prevalence of asymptomatic bacteriuria among the pregnant women receiving antenatal care at Federal Medical Centre Owerri, Nigeria was studied using one hundred and forty urine samples from the pregnant women in the in-patient and outpatient departments. Thirty-five of the women had significant bacteriuria, with a prevalence rate of 25%. The bacteria in the samples were Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Proteus mirabilis. Escherichia coli occurred most frequently (40%) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…A possible explanation behind this increased risk is the bladder compression due to the increased size of the uterus causing residual urinary volume. In contrast to our observation, Onuorah Samuel et al (43) reported that the age and socio-economic conditions contributed enormously in the prevalence of ASB amongst the pregnant women whose urine samples were examined. The prevalence was greater among the out-patients in comparison to the in-patients.…”
Section: Discussioncontrasting
confidence: 99%
“…A possible explanation behind this increased risk is the bladder compression due to the increased size of the uterus causing residual urinary volume. In contrast to our observation, Onuorah Samuel et al (43) reported that the age and socio-economic conditions contributed enormously in the prevalence of ASB amongst the pregnant women whose urine samples were examined. The prevalence was greater among the out-patients in comparison to the in-patients.…”
Section: Discussioncontrasting
confidence: 99%
“…We found most of the cases between 18-30 years of age similar to Onuorah Samuel, 8 it was further confirmed by Ahmad et al in Kashmiri population. 12 Contrary to the above, a study by Bloomberg et al 13 estimated higher prevalence between 31-35 years of age.…”
Section: Resultssupporting
confidence: 88%
“…Studies from Nigeria have shown the burden of ASB to be ranging between 25-45.3%. 8,14 All these studies show that there is a difference in the burden of ASB during pregnancy and these variations might be credited to variances in geographical location, ethnicity, hygienic, cultural and religious norms.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriuria is the presence of bacteria in urine, and if the bacteria in 1 ml of urine exceed 10 5 colony forming units, then irrespective of the presence of symptoms, bacteriuria is considered to be significant. 8 The bacteria that cause urinary tract infections in gravid females are the same as in non-gravid females. Among them, 80-90% of infections are caused by escherichia coli (a gram negative bacillus).…”
Section: Introductionmentioning
confidence: 99%